PENGARUH PER, DER, DAN PBV TERHADAP HARGA SAHAM STUDI PADAN INDEKS SAHAM IDX 80 YANG LISTING DI BEI PERIODE 2022 - Aditya Bayu Kurniawan; Achmad Zaki (Fakultas Ekonomi dan Bisnis, Universitas Wiraraja Madura, 2024)
This study aims to obtain evidence regarding the effect of Debt to Equity Ratio (DER), Price Earning Ratio (PER), and Price Book Value (PBV) on stock prices. The population in this study amounted to 80 companies that were members of the IDX 80 stock index in 2022. This study uses a quantitative method consisting of classical assumption tests and multiple linear regression tests. The hypothesis in this study used a partial test or T test using the help of the SPSS 25 program. The results of this study indicate that the Debt to Equity Ratio (DER) and Price Earning Ratio (PER), have no effect on stock prices, while Price Book Value (PBV) has a significant effect on stock prices.